Studentsâ Linguistic Competence in Essay Writing - Rahmalia, Indah (Institut Agama Islam Negeri Imam Bonjol Padang, 2016)
Writing in a foreign language (English) has been a highly instrumental for EFL Undergraduate learners because they are required to write assignments, papers, and dissertations.Â Yet, the course offered and passed to fulfill the writing requirements was meager especially in the language content.Â Hence, this project aimed at finding out the sentence problem made by the students in essay writing.Â Using 5 data sources from studentsâ writing, the study was focused on exploring studentsâ mistakes in the use of cause-effect.Â Â The finding of this study showed that the most sentences problem made by the students in cause-effect essays were 24 sentences problem in run-on sentences and comma splice and the least were 2 sentences problem in choopy sentences.